Management accounting and risk management practices in financial institutions - Abdul Rasid, Siti Zaleha; Abdul Rahman, Abdul Rahim (Universiti Teknologi Malaysia, 2009)
The aim of this paper is to report the results of a study on management accounting and risk management practices in financial institutions. The research method involved administering a questionnaire to 106 financial institutions listed on the Malaysian Central Bank’s website and the respondents were the chief financial officers (CFO) or the most senior positions in the finance department of the institutions. Based on the IFAC’s (1998) framework, it was found that the most widely practiced were the management accounting practices at Stage 1, followed by practices of Post 1995. This finding shows that despite the emergence of contemporary management accounting practices (Stage 4 onwards), traditional management accounting that focuses on financial performance and budgetary control is still widely practiced by financial institutions in Malaysia. As for the risk management practices, most of the firms have either implemented a complete or partial Enterprise Risk Management (ERM) framework. The findings from the survey showed that management accounting practices related to financial statement and ratio analysis were perceived to contribute most towards risk management. Budgetary control, budgeting and strategic planning were also perceived to be important in managing operational risks.